OBTAINING OF ALKALINE FROM ALUMINATE SOLUTION BY ELECTRODIALYSIS METHOD - Haydarov, A.A.; Alyshanly, G.I.; Kuliyev, S.A.; Mehmet, D.T. (Azerbaijan National Academy of Sciences, 2023)
In the study, electrodialysis of alunite mud and aluminum hydroxide washing solutions, obtained during the processing of alunite ore, has been carried out in the study. Acid and alkali extraction from the electrodialysis process, as well as the conditions for solidification of the obtained alkali and acid, has been researched. PC Cell 64004 electrodialysis device and bipolar, anion, cation exchange membranes and the processes occurring in the membranes has been used in the experiments. Studies show that during the electrodialysis of sodium sulfate solution, if it is possible to obtain a 3–4% sodium hydroxide solution in the initial experiments, the concentration of the alkali can be increased to 5% in the alkali thickening experiments. The flow rate of 1 ml/sec, current strength – 3–4 A, voltage – 4–5 V have been adopted as the optimal conditions of the experiments. During the study of the factors effect on the concentration of the products, it has been determined that the flow rate is the main factor affecting the process. So reducing the flow rate leads to an increase in the concentration of alkali and acid. The longer the sodium sulfate solution remains in the electrolysis chambers, the higher the concentration of the obtains alkali. At the same time, although increasing the current intensity and voltage allows to achieve an increase in the thickness of the products, the rise of these parameters is not considered favorable, since the increase in the current strength has a negative effect on the quality of the membranes. © 2023, Azerbaijan National Academy of Sciences. All rights reserved.
Keywords: acid; alkali; alunite; bipolar membrane; electrodialysis; sodium sulfate